Método de treinamento pré-exaustão e a resposta da atividade eletromiográfica - Reinaldo Juliano de Oliveira Mendes (2012)
Numerous methods of strength training are used today with the intention of promoting gains of hypertrophy and muscle strength. Many of these methods have been developed through the process of trial and error. Even with the lack of an empirical basis, are still used by coaches and practitioners of bodybuilding. Despite the numerous studies conducted by scholars from all over the world, the changes that the different methods of training cause in the muscle and their physiological adaptations are not yet known clearly. Among the various options of training method, we can highlight the method of pre-muscular exhaustion. This training system is to carry out a series of exercise uniarticular before an exercise multiaricular for the same muscle. This study aimed to understand the effects of the method of pre-exhaustion training in the response of the electromyographic activity. For both, a bibliographic survey was carried out considering only experimental studies that investigated the pre-exhaustion method and analyzed the effect of this method in EMG activity. The analysis of the results of articles found revealed some contradictions in the values of the answers of the electromyographic signals muscles analyzed. In general, it was found that contrary to what was thought, the pre-exhaustion method hasnt increased the electromyographic activity of agonist muscles. This contradiction might be explained by training protocols used in experiments. Therefore, considering our limitation in search of literature, further researches are needed to clarify the true effects of the pre-exhaustion method.